A systematic review of the safety of tirzepatide-a new dual GLP1 and GIP agonist - is its safety profile acceptable? - Meng, Zhuqing; Yang, Min; Wen, Haibo; Zhou, Su; Xiong, Chuan; Wang, Yu (Frontiers in Endocrinology, 2023)
Abstract： Aims: Tirzepatide is a novel dual glucose-dependent insulinotropic peptide (GIP) and glucagon-like peptide-1 receptor agonist (GLP-1 RA). At present, there is no controversy over its effectiveness, but its safety. We conducted a systematic review to assess the safety of tirzepatide. Methods: We searched PubMed, Embase and Cochrane databases for randomized controlled trials (RCTs) of tirzepatide from databases inception to August.28 2022 and used the Cochrane Systematic Assessment Manual Risk of Bias Assessment Tool (version 5.1) and modified Jadad scale to assess risk of bias. The systematic review was conducted via Revman5.4. Results: Nine RCTs with a total of 9818 patients. The total safety of tirzepatide is similar to GLP-1RAs, except for the hypoglycemia (tirzepatide 15mg, pooled RR=3.83, 95% CI [1.19- 12.30], P=0.02), discontinuation (tirzepatide 10mg, pooled RR=1.75,95%CI [1.16-2.63], P=0.007 and 15mg, pooled RR=2.03,95%CI [1.37-3.01], P=0.0004). It also showed that the dose escalation could not rise the occurrence rates of total, severe, gastrointestinal adverse events and hypoglycemia (P>0.05); Compared with 5mg, tirzepatide 10mg and 15mg were associated with more frequent nausea (P<0.001), discontinuation (P<0.05) and injection-site reaction (P<0.01); The rates of vomiting and diarrhea were dose-dependence at the range of 5-15mg. Conclusions: The safety profile of tirzepatide is generally acceptable, similar to GLP-1 RAs. It is necessary to pay attention to its special adverse events (hypoglycemia and discontinuation) at high doses (10mg or higher). Nausea, vomiting, diarrhea, discontinuation and injection-site reaction were dose-dependence among specific dose ranges. As the heterogeneity in different studies by interventions, more well-designed trials are needed to control the confounding factors and ensure adequate sample size.